Essential Methods of Plant Sample Preparation for Light Microscopy - Soukup, Aleš; Tylová, Edita (Methods in molecular biology, 2019)
There are various preparatory techniques for light microscopy permitting access to the inner structure of plant body and its development. Minute objects might be processed as whole-mount preparations, while voluminous ones should be separated into smaller pieces. Here we summarize some of the "classical" techniques to cut more voluminous objects into slices and access their inner structure either for simple anatomical analysis or for further processing (e.g., histochemistry, immunohistochemistry, in situ hybridization, enzyme histochemistry).
Keywords: Histocytological Preparation Techniques; Microtomy; histocytologické preparační techniky; Tissue Fixation; barvení a značení; mikroskopie; histocytochemie; mikrotomie; rostliny; Paraffin Embedding; fixace tkání; Microscopy; Staining and Labeling; Plants; zalévání tkání do parafínu; Histocytochemistry